ANALISIS PENERAPAN ISAK 35 PADA ORGANISASI NIRLABA (SD GMIM 4 TONDANO) - Kossay, Edikus (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
This study aimed to analyze the application of Financial Accounting Standards Interpretation (ISAK) 35 concerning the presentation of financial statements for non-profit organizations at GMIM 4 Tondano Elementary School. The approach employed is descriptive qualitative research utilizing interviews, observations, and document organization. The findings indicated that SD GMIM 4 Tondano has started to implement the principles of ISAK 35, but it still encounters challenges related to technical comprehension and human resource capability in creating suitable financial statements that align with the standard. The results offer valuable new perspectives for other non-profit institutions in enhancing the clarity and responsibility of their financial report presentation.